Mechanisms of JARID1B Up-Regulation and Its Role in Helicobacter pylori-Induced Gastric Carcinogenesis - Zheng, Lixin; Wu, Yujiao; Shen, Li; Liang, Xiuming; Yang, Zongcheng; Li, Shuyan; Li, Tongyu; Shang, Wenjing; Shao, Wei; Wang, Yue; Liu, Fen; Ma, Lin; et al. (Frontiers in Oncology, 2021)
Gastric cancer (GC) is the third leading cause of cancer-related death worldwide. Helicobacter pylori (H. pylori) infection can induce GC through a serial cascade of events, with emerging evidence suggesting the important role of epigenetic alterations in the development and progression of the disease. Here, we report on mechanisms responsible for JARID1B up-regulation in GC and its role in the malignant transformation induced by H. pylori infection. We found that up-regulation of JARID1B was associated with poorer prognosis, greater tumor purity and less immune cell infiltration into the tumor. Mechanistically, we showed that the up-regulation of JARID1B in human GC was attributed to JARID1B amplification and its induction by H. pylori infection. Furthermore, we identified miR-29c as a negative regulator of JARID1B in GC. H. pylori caused down-regulation of miR-29c in human GC and thereby contributed to JARID1B up-regulation through relieving post-transcriptional regulation. Functionally, we showed that knockdown of JARID1B reduced GC cell proliferation induced by H. pylori infection. Subsequently, CCND1, a key molecule in GC, was shown to be a target gene of JARID1B. In conclusion, these results suggest that JARID1B may be an oncogene up-regulated in human GC, and could represent a novel therapeutic target to prevent malignant transformation induced by H. pylori infection.